2018
DOI: 10.1111/jfbc.12648
|View full text |Cite
|
Sign up to set email alerts
|

Food protein-derived renin-inhibitory peptides:in vitroandin vivoproperties

Abstract: Renin catalyzes the rate-determining step in the renin-angiotensin-aldosterone system that regulates mammalian blood pressure by converting angiotensinogen to angiotensin I (Ang I). Excessive plasma levels of Ang I is a causative factor in hypertension development. Therefore, inhibition of renin activity can lower blood pressure and provide relief from clinical symptoms associated with hypertension. Synthetic compounds are currently the most used group of renin inhibitors; however, only aliskiren is approved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 62 publications
(75 reference statements)
0
36
0
1
Order By: Relevance
“…Another reason for the development of cardiovascular diseases is hypertension, which causes arteriosclerosis, congestive heart failure, coronary heart disease, end-stage renal diseases, myocardial infarction, and stroke [ 14 ]. The renin–angiotensin system (RAS) has been found to be one of the major regulatory mechanisms in blood pressure regulation [ 15 ]. Within the RAS, renin (EC 3.4.23.15) acts on angiotensinogen to release angiotensin I, which is then cleaved by angiotensin-converting enzyme (ACE) to produce angiotensin II, a potent vasopressor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for the development of cardiovascular diseases is hypertension, which causes arteriosclerosis, congestive heart failure, coronary heart disease, end-stage renal diseases, myocardial infarction, and stroke [ 14 ]. The renin–angiotensin system (RAS) has been found to be one of the major regulatory mechanisms in blood pressure regulation [ 15 ]. Within the RAS, renin (EC 3.4.23.15) acts on angiotensinogen to release angiotensin I, which is then cleaved by angiotensin-converting enzyme (ACE) to produce angiotensin II, a potent vasopressor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ACE (EC 3.4.15.1) and/or renin inhibition help to manage hypertension and offer cardiovascular protection by limiting the physiological level of angiotensin II. Just like obesity and diabetes, current clinical management of hypertension involves mainly the use of drugs, which also have negative side effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 22 peptides had potential hypotensive activity as renin inhibitors. Renin and ACE, two key enzymes in the renin-angiotensin aldosterone system, regulate mammalian blood pressure; renin first converts angiotensinogen to angiotensin 1 which is in turn catalyzed by ACE to angiotensin II, a very powerful vasoconstrictor that simultaneously induces aldosterone secretion, causing increased sodium retention [70]. Although most studies report antihypertensive activity in terms of ACE inhibition, several studies show plant proteins have demonstrated renin inhibitor activity, including canola [71], hempseed [72], lima bean [73], flaxseed [74] and rapeseed [75].…”
Section: Peptide Identificationmentioning
confidence: 99%
“…Functional foods, which can be used for either the treatment or the prevention of hypertension, do not cause the adverse effects of conventional drugs. The employment of these foods may contribute to the reduction of the public health expenditure destined to the cure of cardiovascular diseases (Houston, 2019a(Houston, , 2019b Bioactive peptides of animal and vegetal origin, as well as some components of functional foods, exert anti-hypertensive effects mainly through the inhibition of RAS enzymes and the increase of NO levels (Aluko, 2015a(Aluko, , 2015b(Aluko, , 2019Fritz, Vecchi, Contreras, & Recio, 2011;Martínez-Maqueda, Miralles, Recio, & Hernández-Ledesma, 2012;Quiroga, Aphalo, Nardo, & Añón, 2017;Saleh, Zhang, & Shen, 2014;Wu, Liao, & Udenigwe, 2017).…”
Section: Introductionmentioning
confidence: 99%